How Geometer’s Sketchpad (GSP) Develops Geometry Concept Understanding - Hodiyanto Hodiyanto; Danar Santoso (SAINTIS Publishing, 2020)
The purpose of this study is to show that the development of analytical geometric practicum module based on the application of Geometer Sketpched (GSP) is effective and practical in developing Geometry Concept Understanding. The research method used in this research is research and development. The research subjects in this study consisted of the subject of development and the subject of trials, students of the Mathematics Education Study Program IKIP PGRI Pontianak. Research Procedure: define, design, and development. Data collection tools used in the form of: (1) Validation sheets (2) Questionnaire responses (3) Tests (posttest). The data analysis technique used in this study uses descriptive statistics. Based on the results of research and discussion, in this study it can be concluded that: (1) the practicum module developed is classified as very valid, (2) the practicum module developed is very practical, and (3) the practicum module developed is effective in increasing students' understanding of concepts.